2020
DOI: 10.1029/2019gl086444
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Sudden Stratospheric Warmings on Internal and External Drivers

Abstract: A sudden stratospheric warming (SSW) is a large‐scale disturbance of the wintertime stratosphere, which occurs especially in the Northern Hemisphere. Earlier studies have shown that SSW occurrence depends on atmospheric internal factors and on solar activity. We examine SSW occurrence in northern winters 1957/1958–2016/2017, considering several factors that may affect the SSW occurrence: Quasi‐Biennial Oscillation (QBO), El Niño–Southern Oscillation (ENSO), geomagnetic activity, and solar radiation. We confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 54 publications
4
19
1
Order By: Relevance
“…As such, they support results by Salminen et al. (2020), who showed SSW occurrence rates being modulated by geomagnetic activity during the latter half of the 20th century. SSWs have a substantial impact on winter weather in the Northern Hemisphere by causing cold weather spells to North America and Europe (Baldwin et al., 2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As such, they support results by Salminen et al. (2020), who showed SSW occurrence rates being modulated by geomagnetic activity during the latter half of the 20th century. SSWs have a substantial impact on winter weather in the Northern Hemisphere by causing cold weather spells to North America and Europe (Baldwin et al., 2021).…”
Section: Discussionsupporting
confidence: 91%
“…They hypothesized that the increased planetary wave activity before the SSW favors enhanced wave-mean-flow interaction, which can dynamically amplify the initial polar vortex enhancement caused by the O 3 loss. Furthermore, Salminen et al (2020) show that EEP can significantly influence the occurrence rate of SSWs. The initial pre-conditions such as SSWs are, however, somewhat challenging to account for in the free-running mode, as the EEP impact itself and its dynamical feedback is expected to modulate them.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The steepness also indicates how strongly X increases (b > 0) or decreases (b < 0) the occurrence probability. Recently, Salminen et al (2020) studied the dependence of SSW occurrence rate on several different factors (geomagnetic activity, sunspots, El Niño and QBO). They showed that SSW events occur more often during winters where geomagnetic activity (ap index in December) is low and which are preceded by easterly QBO at 30 hPa in September.…”
Section: Logistic Regressionmentioning
confidence: 99%
“…It was demonstrated that the effect of SSW propagated down to the surface and lasted more than 2 months after the onset of SSW and that the surface pressure signal shifted more toward a negative pattern of the AO (Thompson & Wallace, 1998). The occurrence of SSW was more frequent in the east QBO winters and the effect of the QBO phase on the occurrence of SSW was stronger during the period of low GMA or when the El Niño–Southern Oscillation (ENSO) was in the cold phase (Salminen et al., 2020). According to the results of Asikainen et al.…”
Section: Introductionmentioning
confidence: 99%